Magnesium oxide (MgO) thin film as saturable absorber for passively mode locked erbium-doped fiber laser - Khaleel, Wurood Abdulkhaleq; Sadeq, Sinan Abdulhameed; Alani, Ibrahim Abdulrahman Mahmood; Ahmed, Mahmoud Hazzaa Mohammed (Elsevier, 2019)
A passively mode locked erbium-doped fiber laser (EDFL) operating at center wavelength of 1569.1 nm is demonstrated based on magnesium oxide (MgO) thin film as a saturable absorber (SA) for the first time. MgO SA was constructed using casting solvent method, and it found that it exhibits suitable modulation depth of about 32.4% and saturation intensity of 16 MW/cm 2 . Self-started mode locked pulse trains with fix repetition rate of 3.5 MHz, short pulse duration of 5.6 ps and high signal to noise ratio (SNR) of 50 dB were achieved at maximum input pump power of 159 mW. © 2019